2012
DOI: 10.1007/s00127-012-0581-y
|View full text |Cite
|
Sign up to set email alerts
|

Communication about adherence to long-term antipsychotic prescribing: an observational study of psychiatric practice

Abstract: Patients and psychiatrists work together to create a safe conversational environment in which to discuss this potentially difficult issue. Unlike previous studies of patient reports of psychotic symptoms and side effects of drowsiness being ignored, psychiatrists nearly always respond to disclosures of partial/non-adherence. Psychiatrists should apply the same listening skills to patients' disclosures of troubling side effects and psychotic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…However, our sample of ongoing outpatient consultations may be biased to those encounters where psychiatrists rarely act coercively (Quirk et al . ). Further research is needed to examine more extensively how far psychiatrists attend to their patients’ perspectives in other types of encounters.…”
Section: Resultsmentioning
confidence: 97%
“…However, our sample of ongoing outpatient consultations may be biased to those encounters where psychiatrists rarely act coercively (Quirk et al . ). Further research is needed to examine more extensively how far psychiatrists attend to their patients’ perspectives in other types of encounters.…”
Section: Resultsmentioning
confidence: 97%
“…Psychiatrists' consultations are usually informal and driven by the professional; this avoidance of detailed directed questioning allows any reports of ADRs to be overlooked [111, 112]. Therefore, administration of the ADR Profile by nurses prior to doctors' appointments has potential to bridge this hiatus in care.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and McCabe [38 ▪ ] identified 23 studies relevant to this topic and suggested that future studies should focus on objective assessments of the content of clinical interactions. In one study that did directly assess consultation content, Quirk et al [39 ▪▪ ] analysed recordings of 92 consultations that contained discussion of antipsychotic medications between patients and nine UK psychiatrists. Nonadherence was disclosed in 22 consultations and most frequently resulted in a prescription change in line with the behaviour of the patient [39 ▪▪ ].…”
Section: Nonadherence Is Often a Hidden Problemmentioning
confidence: 99%
“…In one study that did directly assess consultation content, Quirk et al [39 ▪▪ ] analysed recordings of 92 consultations that contained discussion of antipsychotic medications between patients and nine UK psychiatrists. Nonadherence was disclosed in 22 consultations and most frequently resulted in a prescription change in line with the behaviour of the patient [39 ▪▪ ]. The researchers suggest that physicians may avoid risking conflict around medication adherence in order to maintain patients’ engagement with treatment.…”
Section: Nonadherence Is Often a Hidden Problemmentioning
confidence: 99%